Evaluation of 5-year-old children with complete cleft lip and palate: Multicenter study. Part 2: Functional results. Issue 2 (February 2016) - Dissaux, Caroline; Grollemund, Bruno; Bodin, Frédéric; Picard, Arnaud; Vazquez, Marie-Paule; Morand, Béatrice; James, Isabelle; Kauffmann, Isabelle; Bruant-Rodier, Catherine
Abstract: Background and purpose: Cleft surgery is marked by all the controversies and the multiplication of protocols, as it has been shown by the Eurocleft study. The objective of this pilot study is to start a comparison and analyzing procedure between primary surgical protocols in French centers. Methods: Four French centers with different primary surgical protocols for cleft lip and palate repair, have accepted to be involved in this retrospective study. In each center, 20 consecutive patients with complete cleft lip and palate (10 UCLP, 10 BCLP per center), non syndromic, have been evaluated at a mean age of 5 [range, 4–6]. In this second part, maxillary growth and palatine morphology were assessed on clinical examination and on dental casts (Goslon score). Speech was also evaluated clinically (Borel-maisonny classification) and by Aerophonoscope. Results: Veau–Wardill–Killner palatoplasty involves a higher rate of transversal maxillary deficiency and retromaxillary. The fistula rate is statistically lower with tibial periosteum graft hard palate closure but this technique seems to give retromaxillary. Malek and Talmant two-stage-palatoplasty techniques reach Goslon scores of 1 or 2. Considering speech, Sommerlad intravelar veloplasty got higher outcomes. Conclusions: Primary results. Extension to other centers required. The two-stage palatoplasty, including a Sommerlad intravelar veloplasty seems to have the less negative impact on maxillary growth, and to give good speech outcomes. Level of evidence: Therapeutic study. Level III/retrospective multicenter comparative study.